Pencegahan Kekerasan Seksual pada Remaja di Sekolah Menengah Pertama melalui Pemberian Psikoedukasi - Suhadianto, Suhadianto; Ananta, Aliffia (LP2M INSURI Ponorogo, 2023)
The purpose of this service activity is to increase the participants' understanding of the meaning, impact, and strategies for dealing with sexual violence through the provision of psychoeducation. The participants in this activity were 146 junior high school (SMP) students (male = 64 and female = 82). Using PowerPoint media and videos, psychoeducational activities are given using the Student-Centered Learning (SCL) method. The implementation of psychoeducation was divided into two sessions, the first for female students and the second for students. They are technically grouping activity participants based on gender to make it easier for resource persons to convey activity material. Online psychoeducational activities are carried out using the animated video